A tanulók terhelhetőségének vizsgálata a Ruffier- féle teszttel - Greba Ildikó; Греба Ілдіко (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola-„RIK-U” Kft., 2016)
A cikk az iskolások körében felmerülő leggyakoribb egészségügyi rendellenességek egyikét vizsgálja. Továbbá ismerteti a Ruffier- féle teszt alkalmazási lehetőségeit iskolai testnevelés hatékonyságának pontosítása érdekében.

Abstract. In order to accomplish regular physical education at schools it is necessary to monitor the intensity of physical strain. In the present study, the problem of cardiovascular disease as one of the most common health disorders among learners was analysed with the help of the Ruffier test. In physical education, it is recommended to evaluate learners’ load ca-pacity periodically (in autumn and spring) using the Ruffier test. The heart rate measured during the physical loading can provide valuable information to the teacher about the intensity of the given load and the current state of children’s health.
The investigation of learners’ load capacity by the Ruffier test
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00006449
Keywords: állóképesség; testnevelési kategória; egészséges testi fejlődés; teljesítőképesség